2007
DOI: 10.1016/j.molimm.2007.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Epi-allelic Erk1 and Erk2 knockdown series for quantitative analysis of T cell Erk regulation and IL-2 production

Abstract: Erk activation is often used as a downstream pathway indicator of TCR signaling, generally in terms of both Erk1 and Erk2 isoforms measured together. In order to investigate potential distinctions between Erk1 and Erk2 regulation and effects downstream of TCR ligation, we generated a series of stable and independent Erk1 and Erk2 shRNA knockdown lines in the 1B6 T cell hybridoma. We observed no compensatory effect by opposite isoform upregulation, and found similar fractions of total phosphorylated Erk1/2 acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…We examined the association between VDR upregulation and ERK1/2 given the known importance of MAPK signaling in human T cell activation and IL-2 production [32]. Our finding that phosphorylation of ERK1/2 precedes expression of VDR strictly on p-ERK1/2+ cells suggests a possible role for the ERK1/2 pathway in VDR upregulation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We examined the association between VDR upregulation and ERK1/2 given the known importance of MAPK signaling in human T cell activation and IL-2 production [32]. Our finding that phosphorylation of ERK1/2 precedes expression of VDR strictly on p-ERK1/2+ cells suggests a possible role for the ERK1/2 pathway in VDR upregulation.…”
Section: Discussionmentioning
confidence: 98%
“…Prior studies have demonstrated that GVHD-inducing alloreactivity is mediated primarily by naïve and possibly early memory T cells [29,30] and also may depend on ERK1/2 activation [31], which is important for IL-2 production [32]. Therefore, we developed an approach to assess VDR and p-ERK1/2 simultaneously, and examined the maturation stage dependence of VDR upregulation.…”
Section: Vdr Upregulation Is Associated With Erk1/2 Phosphorylation Amentioning
confidence: 99%
“…The forward and reverse primers (1 l each of 1 g/l) (see Table S2 in the supplemental material) were annealed (28), and the annealed oligonucleotides were ligated into pLL3.7 through HpaI and XhoI sites. An shRNA that targets the luciferase gene was used as a control (31). Lentiviruses were generated as previously described (28).…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, siRNA offers the advantage of isoform specificity and enable fine-tuning of individual isoform expression and activity. For an investigation of T-cell Erk regulation, researchers used epi-allelic series with siRNAs against ERK1 and ERK2 to identify the role of these kinases on downstream IL-2 production [17]. The epi-allelic series again showed a correlation between siRNA targeting efficiency and phenotype.…”
Section: Rnai Screens As a Tool For Cancer Biologymentioning
confidence: 99%